A report of a counselling internship undertaken at the Memorial University Counselling Centre, with a report of a research study assessing the effectiveness of an assertion training programme - Pinsent, Stephen Michael, 1952- (1980)
Thesis (M.Ed.) -- Memorial University of Newfoundland, 1980. Counselling Centre Bibliography : leaves 77-92.